Electric Vehicle Batteries: Technical and Environmental Aspects - Olishevska, V. E.; Olishevskyi, H. S.; Ivanova, H. P. (Science and Transport Progress, 2025)
Purpose. The transition to electric vehicles can be considered a promising direction for the development of motor transport, and one of the key elements that ensures the functioning and determines the prospects for the development of electric vehicles is batteries. The main objective of this work is to study the technical and environmental aspects of the production, operation, and disposal of electric vehicle batteries in Ukraine. Methodology. To assess the impact of batteries on the development of electric vehicles, it is advisable to study their production, operation, and decommissioning (disposal). Today, the main problems associated with electric vehicle batteries at the production stage are: the need to use critical raw materials; difficulties in producing high-capacity and inexpensive batteries; improving the basic parameters of batteries; and environmental pollution. During the operation stage, important challenges include changes in battery parameters and the decarbonization of the electricity used during operation. Decommissioning batteries is a difficult task because many different materials are used in the production of components, and different technologies are required for their recycling at the disposal stage. Finding. The current state, technical, and environmental aspects related to the production, operation, and disposal of electric vehicle batteries are analyzed. It is shown that batteries significantly affect the cost of electric vehicles, determine their mileage and ease of use, and have an environmental impact. It is emphasized that secondary batteries (second-life batteries) can be used to create energy storage systems, charging stations for electric vehicles, and microgrid energy systems. Originality. A comprehensive analysis of the problems of production, operation, and recycling of rechargeable batteries was carried out, which allows identifying their impact on the competitiveness, cost-effectiveness, and environmental friendliness of electric vehicles. The main trends in the development of electric vehicle rechargeable batteries in Ukraine were identified. The problems of manufacturing and recycling rechargeable batteries were considered. It is emphasized that the development of innovative technologies for the creation of efficient, safe, and affordable rechargeable batteries is an important step towards the transition to environmentally friendly transport in Ukraine. Practical value. The main trends in the use of electric vehicle rechargeable batteries that can be developed in Ukraine are identified, and the problems of their manufacture and recycling are considered.